BILATERAL PSOAS ABSCESS AFTER EXTRACORPOREAL SHOCK WAVE LITHOTRIPSY: REMINDER OF A RARE COMPLICATION - Zafar, Sidra; Bin Mahmood, Syed Usman; Tharwani, Arsal; Nasir, Noreen (Journal of Ayub Medical College Abbottabad, 2018)
Extracorporeal shock wave lithotripsy (ESWL) is among the most widely used modalities for treatment of urolithiasis since its introduction in the 1980s. The non-invasive technique reduces the risk of post-procedure complications and produces excellent stone free rates. However, complications may still follow and albeit rare, there are reports in literature of abscess formation post ESWL. Herein, we report the case of a young, immunocompetent gentleman who developed bilateral psoas abscess after undergoing this procedure. He was successfully managed at our institute with intravenous antibiotics, percutaneous abscess drainage and was discharged on day 5 post-intervention in a stable condition. There have been two similar cases reported in literature. Keywords: Extracorporeal shock wave lithotripsy, ESWL; Psoas abscess; abscess, Complication